2016
DOI: 10.11604/pamj.2016.23.35.7841
|View full text |Cite
|
Sign up to set email alerts
|

Plastibell circumcision of 2,276 male infants: a multi-centre study

Abstract: IntroductionThe World Health Organization's manual on male circumcision listed Plastibell technique as a well-proven paediatric method with respect to the results and complications. Although, literatures abound on its wide acceptability, there are few multi-centered reports from this environment. The objective was to evaluate the cases of infant circumcision by Plastibell device from two medical institutions.MethodsAll consecutive infants who had Classical Plastibell Circumcision (PC) at the Federal Staff Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 29 publications
4
49
1
Order By: Relevance
“…In their 1981 review, Warner and Strashin noted ranges from as low as 0.06% to a high of 55% reported by Kingston General Hospital. 24,35 This seems to be the trend in the literature; several large series from different parts of the world recorded similar low complication rates: In Israel, Ben Chaim et al report 1.2%; 32 in Nigeria, Biuko et al report 1.1%; 30 and in the U.S., El-Bcheraoul et al report 0.5%. 8 In their study, El-Bcheraoul et al concluded that male circumcision had a low incidence of adverse events overall, especially if the procedure was performed during the first year of life, but rose 10-20-fold when performed after infancy.…”
Section: Complicationsmentioning
confidence: 67%
See 2 more Smart Citations
“…In their 1981 review, Warner and Strashin noted ranges from as low as 0.06% to a high of 55% reported by Kingston General Hospital. 24,35 This seems to be the trend in the literature; several large series from different parts of the world recorded similar low complication rates: In Israel, Ben Chaim et al report 1.2%; 32 in Nigeria, Biuko et al report 1.1%; 30 and in the U.S., El-Bcheraoul et al report 0.5%. 8 In their study, El-Bcheraoul et al concluded that male circumcision had a low incidence of adverse events overall, especially if the procedure was performed during the first year of life, but rose 10-20-fold when performed after infancy.…”
Section: Complicationsmentioning
confidence: 67%
“…Complication rates are usually minor (0.2-2.0%). 8,[29][30][31][32] Parents are aware of the requirements and rituals in their various ethnic groups and religions are often anxious to secure access for an acceptable facility and date for the circumcision.…”
Section: Preferred Age For Childhood Circumcisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies had documented that the residual plastic ring usually falls off within 10 days of the procedure, while the ring separates faster in neonates due to thin prepuce and easier sloughing. [13][14][15] . The mean surgical time in our study was 4±2 mins which is comparable with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The mean surgical time in our study was 4±2 mins which is comparable with other studies. 12,14 The technique of Plastibell circumcision had established itself as an acceptable form of circumcision particularly in neonates to one-year old infants. Complications with this technique were reported to be 2% to 3%.…”
Section: Discussionmentioning
confidence: 99%